Chirality amplification in helical block copolymers. Synthesis and chiroptical properties of block copolymers of chiral/achiral acetylene monomers1. Issue 32 (28th August 2015) - Kumazawa, Shohei; Rodriguez Castanon, Jesus; Shiotsuki, Masashi; Sato, Takahiro; Sanda, Fumio
<x xml:space="preserve">Abstract</x> Block copolymers of N-tert-butoxycarbonyl-l-valine 4-ethynylanilide (1a) and N-tert-butoxycarbonylglycine 4-ethynylanilide (1b) with various compositions were synthesized by block copolymerization using a [(nbd)RhC(Ph){CPh2(PPh3)]/PPh3 catalyst.